posted by Leanna .
If the function f is defined by f(x)=x^2-2x, find limit h->0
first, f(3+h)=(3+h)^2 -2(3+h)
= 9+6h+h^2-6-2h = h^2+4h+3= (h+3)(h+1)
second f(3-h)=(3-h)^2 -2(3-h)=
so first -second then is
finally, lim 8h/2h=4
check all that.
Thank you for your help!
For the second part I thought it would be -(9+6h-h^2)-6+2h?
you put a minus sign in front of the first term? Why?
and, the 6h term in (3-h)^2=9-6h+h^2
I put a minus sign because it has a negative in front of the f(3-h) so it's -(f(3-h))